Desain dan Simulasi Jaringan Wireless Menggunakan Ekahau pada Area Perkantoran - Faisal Nur Rochman (Jurnal Multidisiplin Indonesia, 2026)
The need for a stable and quality wireless network in the office environment is increasing, along with the high use of internet-based applications such as video conferencing, digital collaboration, and online business systems. However, many Wi-Fi network implementations  in enterprises are still carried out without proper planning, resulting in problems such as dead zones, interference, and network capacity that does not meet the needs of users. This research aims to design and simulate wireless networks  using Ekahau AI Pro software, which is  a professional tool for predictive modeling-based Wi-Fi  network design. The research methods include environmental data collection, office area modeling, device needs, coverage simulation, interference analysis, and network capacity calculation. The results of the simulation include  signal heatmaps, SNR analysis, user capacity predictions, and  recommendations for optimal Access Point placement  . This research is expected to provide a clear picture of the process of designing modern wireless networks  and help companies improve network performance without having to do trial and error in the field. In addition, this research can also be an academic reference for TRKJ students in studying wireless network planning based on simulation software.